2009
DOI: 10.1161/circulationaha.108.808907
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Novel Solution, Somah, for the Procurement and Preservation of Beating and Nonbeating Donor Hearts for Transplantation

Abstract: Background-Injury to myocytes, endocardium, and the coronary endothelium during harvesting and storage can compromise outcomes after heart transplantation. Safeguarding of structure and function of cardiomyocytes and endothelium in donor hearts may lead to improved patient survival after transplantation. Information gained from porcine hearts stored in standard transplant solution was used to design a superior preservation solution that would optimally protect and maintain organs from beating heart and/or nonb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…8,9 Some organ preservation solutions have been developed and applied in transplantation, but cold ischemic storage of the heart is still limited to 4 to 6 hours because preservation solutions have been unable to significantly inhibit the ensuing I/R injury. 10 Cx43, as an important player in the pathophysiology of myocardial I/R injury, has a role in protection during ischemic and pharmacologic pre-conditioning. 11 Using a transgenic mouse model, Roell et al reported that cardiac engraftment of Cx43-overexpressing myoblasts in vivo prevents post-infarct arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Some organ preservation solutions have been developed and applied in transplantation, but cold ischemic storage of the heart is still limited to 4 to 6 hours because preservation solutions have been unable to significantly inhibit the ensuing I/R injury. 10 Cx43, as an important player in the pathophysiology of myocardial I/R injury, has a role in protection during ischemic and pharmacologic pre-conditioning. 11 Using a transgenic mouse model, Roell et al reported that cardiac engraftment of Cx43-overexpressing myoblasts in vivo prevents post-infarct arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…A paradigm shift is emerging in the field, with a new focus on providing organs with necessary metabolic nutrients instead of slowing metabolism. Somah solution attempts to meet the energy requirements of cardiomyocytes and coronary endothelium by preserving anaerobic metabolism and high-energy phosphates, while safeguarding the mitochondrial gradient [33]. Interestingly, the Somah solution is most effective at 21°C [34], adding to the question whether conventional low ex vivo storage temperature is justified.…”
Section: Organ Storage Solutionsmentioning
confidence: 99%
“…While investigating the role of our novel heart storage solution in a porcine orthotopic heart transplant model, we observed the development of unusual signs of hypermetabolism and multi-systemic involvement in both the donors and recipients [8]. Anesthetic used in these surgeries was inhalational isoflurane and the severity of observed signs was found to be proportional to duration of anesthesia.…”
Section: Introductionmentioning
confidence: 96%